Local Government behavior and principal - agent theory - Ana Bela Santos Bravo; António Luís Silvestre (European Regional Science Association (ERSA), 2004)
This paper aims at presenting a simple model of local decision-making based on the hypothesis of “constrained” monopoly power on the part of local governments. It adds the contribution of the principal-agent theory by assuming that: (a) monopolistic behavior is constrained by voters' efforts to monitor the outcomes of policies; (b) local governments' policies affect local property values. An empirical test of the model for the Portuguese local authorities indicates that the hypothesis of “monitoring” may be accepted and that of capitalization can only be accepted in relation to local public services not to local taxes on property.
Keywords: 330